An Analysis on Students’ Attitude Toward English for Islamic Psychology - Hasanah, Imroatul (Happiness: Journal of Psychology and Islamic Science, 2019)
English for Specific Purpose (ESP) is a compulsory subject in study program of Islamic Psychology at IAIN Kediri named Study of English Texts. The goals of ESP are students able to read Islamic-Psychological English texts comprehensively and explain them in presentation forum. The goals seem achieved far from expectation. Hence, conducting the research to know the students’ attitude toward the subject is necessary since their attitude is tightly related to their successful learning. In conducting the research, the researcher used survey method by using SPSS 24 for calculating the numerical data gained by the questionnaires shared to 165 samples. The researcher adapted Shelley’s (2001) steps for the research: 1) defining the problem, identifying the population, determining the variables, 2) determining the collecting data by using paper-based questionnaire, 3) determining a sampling plan by using Slovin's Formula, 4) developing the questionnaire, 5) spreading the questionnaires out to Islamic Psychology Department students, 6) editing and processing the data, and 7) analyzing the data. The data were collected by using questionnaires containing a set of demografic questions and agreement on statements of attitudes toward ESP Course. Also, it was developed with considering the general positive, negative and neutral attitudes. Each question or statement leaded to certain attitudes. A set of questionnaire with 35 items together with the responses used Likert Scale. There were 5 scales. Scale 1 was for strongly disagree, scale 2 was for disagree, scale 3 was for neutral, scale 4 was for agree, and scale 5 was for strongly agree. Based on the data gained from SPSS 24 calculation, the mean was 128 of all total score 175. In other words, there were 73% of all samples showed the positive attitudes toward ESP Course. Meanwhile, the kinds of positive attitudes having by the students were confidence, optimism, cheerfulness, happiness, sincerity, sense of responsibility, reliability, tolerance, willingness to adapt, humility and diligence. Those were represented in the statements of the questionnaires shared. In the other words, the students’ attitudes could be seen from the answers they stated in the questionnaires.